The crisis of love in Michel Houellebecq's Sérotonine. (14th June 2022) - Refsum, Christian
Abstract: In this article I argue that Michel Houellebecq's novelistic descriptions of isolated and depressed protagonists in Sérotonine (2019) and in his earlier novels should not simply be read as symptomatic of the crisis of love in late capitalism. By focusing on situations where love might or might not manifest itself, Houellebecq also explores the potentiality of love. Despite the vast reception of Houellebecq's poems and novels, his critics have not sufficiently understood how the love theme is central throughout his work. This article explains its significance by focusing on Sérotonine and drawing lines to the earlier novels. In Sérotonine, as in Soumission (2016), the potentiality of love is closely related to an ambivalent pondering on the threshold of religion. Both novels have protagonists characterised by avoidance, negativity and indecisiveness. Love is both a potential and a testing ground for survival, on a personal as well as on a cultural level.